Stability Mechanism and Control Factors on Equipment Removal Area under “Goaf-Roof-Coal” Structure - Zhongshun Chen; Yong Yuan; Cheng Zhu; Wenmiao Wang (Advances in Civil Engineering)
One of the main difficulties in longwall mining (LM) is the movement of mining equipment from one panel to the next panel during mining process. The shields of the LM face may be damaged by the collapse of the roof in shallow coal seam under the “Goaf-Roof-Coal” (GRC) structure, especially when moving the shields from the current panel to the next panel. In order to solve this problem, the stability mechanism and its control factors during the LM equipment removal were investigated by using comprehensive methods including theoretical analysis, numerical simulation, and field validation based on the working conditions of Panel 31102 in Liangshuijing Coal Mine. The numerical simulations demonstrate that four different failure zones, shear failure zone, tension failure zone, partly elastic zone, and plastic failure zone, appear around the area due to the position of rock and the arrangements of the supports. The shear failure zone, which is controlled by shield working resistance and roof supporting strength, is the main cause of the failure in the removal area. To minimize the shear failure zone, several measures such as optimizing the end position for LM face, decreasing the width of removal area, and increasing the amount of cable support were taken to ensure the stability of surrounding rock in removal area, which have successfully controlled the damage of roof and equipment in Panel 31102. The field observation confirms that the proposed stability mechanism and control measures are effective under GRC structure.